2020
DOI: 10.1186/s12917-020-02425-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and antibiotic resistance profiling of Salmonella species isolated from chickens in eastern Turkey

Abstract: Background: The aim of this study was to obtain quantitative data about the frequency, genotypic characterization and antibiotic resistance profiling of Salmonella agents in chicken flocks located in eastern Turkey. Results: Feces samples representing at least 20% of the flock area were collected via sock swabs from commercial poultry flocks in the study region in addition to internal organs (liver, spleen, intestine) collected at necropsy of suspected chickens belonging to small family enterprises. The sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
17
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 41 publications
4
17
0
Order By: Relevance
“…Enteritidis (21.9%) and S . Typhimurium (9.4%) were isolated from chicken in Turkey [ 82 ]; Salmonella enterica serovars were identified in backyard poultry flocks in India [ 83 ]; S . Enteritidis and S .…”
Section: Discussionmentioning
confidence: 99%
“…Enteritidis (21.9%) and S . Typhimurium (9.4%) were isolated from chicken in Turkey [ 82 ]; Salmonella enterica serovars were identified in backyard poultry flocks in India [ 83 ]; S . Enteritidis and S .…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, streptomycin resistance gene (strA/B) was isolated in serovars of NTS with reliable prevalence rate. Arkali and Çetinkaya, (2020) detected 58% positive sul1 gene from the Salmonella isolates of chickens in eastern Turkey. In our study, harmonic and proportioned correlation were existent between genotypic and phenotypic resistance decoration.…”
Section: Discussionmentioning
confidence: 97%
“…The higher occurrence of S. Typhimurium in our study is synchronized with findings at home and abroad. Consecutively, S. Typhimurium and S. Enteritidis were isolated from raw chicken meat at retail markets in Malaysia (Thung et al, 2018); higher prevalence of S. Enteritidis (21.9%) and S. Typhimurium (9.4%) were isolated from chicken in Turkey (Arkali et al, 2020); Salmonella enterica serovars were identified in backyard poultry flocks in India (Samanta et al, 2014); S. Enteritidis and S. Typhimurium recovered from chicken meat in Egypt (Tarabees et al, 2017). Similarly, Suresh et al (2006) recovered S.…”
Section: Discussionmentioning
confidence: 99%
“…In Malaysia, S. Typhimurium and S. Enteritidis were isolated from raw chicken meat at retail markets [70]. In Turkey, the prevalent serotype was identified as S. Enteritidis (21.9%) and S. Typhimurium (9.4%) from chicken [72]. In India, Salmonella enterica serovars were isolated from backyard poultry flocks [73].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, ESBL are usually encoded by large plasmids that are transferable from strain to strain and between bacterial species [96,100]. Arkali and Çetinkaya [72] detected sul1 gene with 58% among the Salmonella isolates from chickens in eastern Turkey. Consequently, Jahantigh et al [101] isolated the most prevalent tetA from broiler chicken in Iran.…”
Section: Discussionmentioning
confidence: 99%